2014
DOI: 10.1021/jo402677w
|View full text |Cite
|
Sign up to set email alerts
|

Isotopologue Profiling of Triterpene Formation under Physiological Conditions. Biosynthesis of Lupeol-3-(3′-R-hydroxy)-stearate in Pentalinon andrieuxii

Abstract: The biosynthesis of lupeol-3-(3'R-hydroxy)-stearate (procrim b, 1) was investigated in the Mexican medicinal plant Pentalinon andrieuxii by (13)CO2 pulse-chase experiments. NMR analyses revealed positional enrichments of (13)C2-isotopologues in both the triterpenoid and the hydroxystearate moieties of 1. Five of the six isoprene units reflected a pattern with [1,2-(13)C2]- and [3,5-(13)C2]-isotopologues from the respective C5-precursors, IPP and DMAPP, whereas one isoprene unit in the ring E of 1 showed only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…) has stimulated an interest for understanding its biosynthetic origin. Initial attempts to incorporate labeled precursors into the sesquiterpenoid carbon have resulted in the isolation of labeled terpenoids but not of labeled UA , emphasizing the importance of learning more about the production dynamics of UA during plant development. The results of this investigation showed that, while UA could not be detected in root tissue during the first stage of plant development ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…) has stimulated an interest for understanding its biosynthetic origin. Initial attempts to incorporate labeled precursors into the sesquiterpenoid carbon have resulted in the isolation of labeled terpenoids but not of labeled UA , emphasizing the importance of learning more about the production dynamics of UA during plant development. The results of this investigation showed that, while UA could not be detected in root tissue during the first stage of plant development ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, metabolic cross-talk between the two pathways of terpenoid backbone biosynthesis is well documented (Bartram et al, 2006;Opitz et al, 2014;Peña-Rodríguez et al 2014;Rodriguez-Concepción and Boronat, 2015;Skorupinska-Tudek et al, 2008) (Figure 1). Therefore, the relative contribution of each pathway to the biosynthesis of the various classes of terpenes or even of a specific plant terpenoid remains uncertain and could depend on the given plant species or environmental conditions (Vranová et al, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Triterpene is formed from squalene via cyclization process involving the tail condensation of farnesol, which has been confirmed to have antibiofilm activity (Pena‐Rodriguez et al . ). Horev et al .…”
Section: Introductionmentioning
confidence: 97%
“…Ginseng extract ginsenosides are derived from a series of triterpenoid saponins compounds (Qu et al 2011). Triterpene is formed from squalene via cyclization process involving the tail condensation of farnesol, which has been confirmed to have antibiofilm activity (Pena-Rodriguez et al 2014). Horev et al (2015) reported that topical application of farnesol-loaded nanoparticles impeded biofilm formation by Streptococcus mutans and distinctly attenuated the virulence of this species in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%